Warfarin-Related Nephropathy Modeled by Nephron Reduction and Excessive Anticoagulation - Ware, Kyle (American Society of Nephrology, 2011)
An acute increase in international normalized ratio (INR) to >3.0 in patients with chronic kidney disease (CKD) can associate with an unexplained acute increase in serum creatinine and accelerated progression of CKD. A subset of these patients have renal tubular obstruction by casts of red blood cells, presumably the dominant mechanism of the acute kidney injury described as warfarin-related nephropathy. Here, we developed an animal model of this acute kidney injury that is based on the 5/6-nephrectomy model to aid future investigation of the pathogenesis of this condition. We found that acute excessive anticoagulation with brodifacoum (“superwarfarin”) increased serum creatinine levels and hematuria in 5/6-nephrectomized rats but not in controls. In addition, morphologic findings in 5/6-nephrectomized rats included glomerular hemorrhage, occlusive red blood cell casts, and acute tubular injury, similar to the biopsy findings among affected patients. Furthermore, in the rat model, we observed an increase in apoptosis of glomerular endothelial cells. In summary, the 5/6-nephrectomy model combined with excessive anticoagulation may be a useful tool to study the pathogenesis of warfarin-related nephropathy.